2002
DOI: 10.1007/s00330-002-1602-0
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided laser-induced thermotherapy with a cooled power laser system: a case report of a patient with a recurrent carcinoid metastasis in the breast

Abstract: We report a case of a 52-year-old woman with a palpable recurrent metastasis of a neuroendocrine carcinoma to the upper outer quadrant of the right breast. For the treatment of this lesion, MR-guided laser-induced thermotherapy was performed with a cooled power laser system (Nd:YAG-Laser). An open 0.2-T MR unit was used for the monitoring of the laser energy delivery to the breast; thus, a thermosensitive fast low-angle shot 2D sequence for MR thermometry was used, so the ablation of the tumor and the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Authors have performed breast LITT using imaging systems at field strengths as low as 0.2 T. 28 The overall complete tumor ablation in the literature ranges between 13% and 76%. 16 Mumtaz et al 26 performed the first study using LITT to treat 20 breast cancer patients guided by MRI, followed by surgery.…”
Section: Rfamentioning
confidence: 99%
See 2 more Smart Citations
“…Authors have performed breast LITT using imaging systems at field strengths as low as 0.2 T. 28 The overall complete tumor ablation in the literature ranges between 13% and 76%. 16 Mumtaz et al 26 performed the first study using LITT to treat 20 breast cancer patients guided by MRI, followed by surgery.…”
Section: Rfamentioning
confidence: 99%
“…Authors have performed breast LITT using imaging systems at field strengths as low as 0.2 T . The overall complete tumor ablation in the literature ranges between 13% and 76% …”
Section: Littmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of MRI systems at field strengths as low as 0.2T have been reported for targeting and monitoring [49]. Mumtaz et al [46] correlated pre- and post-procedural MRI with histopathology in a study of 20 women with proven breast cancer.…”
Section: Mr-guided Laser Interstitial Thermal Therapies (Litt)mentioning
confidence: 99%
“…However, a limitation often encountered with interstitial therapies is unintentional charring at the surface of the diffusers [7]. In a Phase I clinical trial of 899 patients with a total of 2,520 lesions, it was found that MR-guided ILH with local anesthesia was safe, yielding acceptably low rates of major complications, however, the treatment at times required internally cooled diffusers [8]. The unintentional charring was partially attributed to hot spots in the fiber emission.…”
Section: Introductionmentioning
confidence: 99%